PENGEMBANGAN MEDIA PEMBELAJARAN BERBENTUK COMPACT DISC BERORIENTASI PENDEKATAN KONSEP PADA MATERI SEL - Hendra Lardiman (Journal on Education, 2019)
The aim this study to create a new learning process, that can increase student’s understanding the concept of cell’s material. The purpose of this study was to develop valid, practical and effective biology’s learning media that oriented to concept approach at cell’s material in interactive compact disc (CD) form. The type of this research was the development research. Model and procedure development using 4-D (four-D-Model) without disseminate phase. Phase consists of phase define, design, and develop phase. Define phase involves analysis of curriculum, students, concept, and media. In design phase, the media (interactive CD) that oriented to concept approach was designed based on define phase. In develop phase, the validation of media was done by some experts, and limited testing for students in Senior High School (SMA 2) Sungai Penuh grade XI. The results of the study showed that the interactive CD oriented concept approach was valid. The value of validation was 3,29 whith valid criteria. Conclusion The study is an interactive CD oriented approach to the concept of cell material for class XI otherwise very valid, practical and effective for use in the learning process